2009
DOI: 10.1186/1423-0127-16-15
|View full text |Cite
|
Sign up to set email alerts
|

Partially hydrolyzed guar gum supplement reduces high-fat diet increased blood lipids and oxidative stress and ameliorates FeCl3-induced acute arterial injury in hamsters

Abstract: Increased reactive oxygen species (ROS) and hyperlipidemia can promote arterial thrombus. We evaluated the potential of a partially hydrolyzed guar gum (PHGG) as dietary fiber on lipid profiles and FeCl 3 -induced arterial thrombosis in the high fat-diet fed hamsters. Our in vitro results found that PHGG is efficient to scavenge O 2 -•, H 2 O 2 , and HOCl. High fat-diet increased plasma triglyceride, total cholesterol, LDL, VLDL, methylguanidine and dityrosine level and accelerated FeCl 3 -induced arterial thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…The rat model of topical ferric chloride (FeCl 3 )-induced carotid artery or femoral artery thrombosis (peripheral artery occlusive diseases) has been used extensively to assess the antithrombotic activities of test agents. 4,8 To easily monitor blood flow and obtain larger tissue sampling, we selected a carotid artery thrombosis model. We placed a flow probe (Probe 0.5VBB517, Transonic Systems, Inc, Ithaca, NY) in the left carotid artery for measurement of arterial blood flow in the anesthetized rats.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat model of topical ferric chloride (FeCl 3 )-induced carotid artery or femoral artery thrombosis (peripheral artery occlusive diseases) has been used extensively to assess the antithrombotic activities of test agents. 4,8 To easily monitor blood flow and obtain larger tissue sampling, we selected a carotid artery thrombosis model. We placed a flow probe (Probe 0.5VBB517, Transonic Systems, Inc, Ithaca, NY) in the left carotid artery for measurement of arterial blood flow in the anesthetized rats.…”
Section: Animalsmentioning
confidence: 99%
“…[1][2][3] Locally exaggerated vascular ROS decrease the bioavailability of nitric oxide (NO), impair vascular relaxation, and increase leukocyte or platelet adhesion and aggregation in injured vessels. 3,4 ROS can increase fractalkine chemokine (C-X3-C motif) ligand 1 (CX3CL1) and intercellular adhesion molecule-1 (ICAM-1) expressions on injured endothelium, attract fractalkine receptor (CX3CR1)-expression inflammatory cells to the inflamed area, 5 and provoke atherosclerosis and vascular inflammation. 6 Increased ROS may induce endoplasmic reticulum (ER) stress to trigger cellular apoptosis 7 and overexpress proapoptotic p53 to trigger endothelial apoptosis and vascular dysfunction.…”
mentioning
confidence: 99%
“…Locally vascular ROS formation inhibited the bioavailability of nitric oxide (NO), impaired vascular relaxation, and increased leukocytes, platelets and fibrin adhesion to and aggregation in injured vessels [23,24]. ROS can increase fractalkine (CX3CL1) and ICAM-1 expressions on injured endothelium, attract fractalkine receptor (CX3CR1)-expression inflammatory cells to the inflamed area, and provoke atherosclerosis and vascular inflammation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Kuo et al [27] have reported that dietary supplementation with PHGG in hamsters fed with high unsaturated fat diet reduced plasma cholesterol and lipid profiles. Other researchers found that PHGG supplementation decreased cholesterol and lipid levels, thus it has a potential to prevent hypertension and cardiovascular diseases [28][29][30].…”
Section: Effect On Blood Cholesterolmentioning
confidence: 99%